177k views
3 votes
What is the solution to this system of linear equations?

2x + y = 1
3x - y = -6
© (-1,3)
(1,-1)
0 (2, 3)
(5,0)

User Itowlson
by
6.0k points

1 Answer

5 votes

Answer:

(-1,3)

Explanation:

Start with combining the two equations.

2x + 3x = 5x

y-y=0

1-6=5

so the equation is now:

5x=-5

now divide the left side to the right, only the number though not the variable. so no it is. x=-1.

Well. the normal coordinate is (x,y).

Right now we have (-1,y)

We now just need to find the Y. To do that:

1) plug the value of x back into any equation. the bottom or top. (DO NOT COMBINE THE EQUATIONS NOW)

so you have 2x + y =1

(insert value) 2(-1) + y = 1

the equation is now -2 + y = 1

add 2 to both sides to have y by itself

y = 3.

so your final answer is (-1,3)

User MarkRoland
by
6.2k points